2014
DOI: 10.1007/s10029-014-1221-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the abdominal musculo-aponeurotic anatomy in rectus diastasis: comparison of CT scanning and preoperative clinical assessment with direct measurement intraoperatively

Abstract: Clinical assessment prior to surgery provides more accurate information than CT scanning in the assessment of ARD width. CT scanning underestimates ARD width when compared with intraoperative measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…If the symptoms from ARD emanate from a decrease in abdominal wall muscle strength, it should be possible to determine a correlation between the width of the ARD and abdominal muscle strength. As shown previously [6,] the correlation between the ARD width estimated clinically using a tape measure and that estimated by CT scan is low. The intraoperative finding was regarded as the ‘true' ARD width, and that correlated fairly well with preoperative clinical assessment using a tape measure.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…If the symptoms from ARD emanate from a decrease in abdominal wall muscle strength, it should be possible to determine a correlation between the width of the ARD and abdominal muscle strength. As shown previously [6,] the correlation between the ARD width estimated clinically using a tape measure and that estimated by CT scan is low. The intraoperative finding was regarded as the ‘true' ARD width, and that correlated fairly well with preoperative clinical assessment using a tape measure.…”
Section: Introductionmentioning
confidence: 85%
“…Since muscle strength may be assumed to affect the patient's functional symptoms, our findings support the use of ARD width as one of the criteria for surgical treatment. Even if this study showed no significant correlation between preoperative clinical ARD width assessment and muscle strength, this is the method that hitherto has been shown to best approximate intraoperative ARD width (‘true' width) in the lower midline [6]. …”
Section: Discussionmentioning
confidence: 99%
“…The condition is often characterized by bulging or sagging in the abdominal midline during abdominal muscle contraction. Although no consensus regarding the definition of DRA exists, it is often defined in the literature as separation of the recti greater than 22–30 mm.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with intraoperative findings also, US meas urement has proven reliable, particularly in the abovena vel area, while at the belownavel level there is a slight tendency to underestimate the separation between the two muscles [24,29]. The same applies to MRI [30] meas urements and to CT [31] measurements, both of which underestimate somehow the extent of muscles separation [32,33]. The minor discrepancies found between preop eratory measures, including imaging modalities other than US, and intraoperatory measures are possibly due to the muscle tone relaxation during general anaesthesia [32].…”
mentioning
confidence: 99%